Design and development of tractor-drawn onion (Allium cepa) harvester - KHURA, TAPAN KUMAR; MANI, INDRA; SRIVASTAVA, A P (The Indian Journal of Agricultural Sciences, 2011)
The commonly used manual harvesting of onion (Allium cepa L.) is time consuming, less efficient and full of drudgery so the mechanization of onion harvesting is essentially needed. Various crop-machine and operational variables related to design of mechanical onion harvester were evaluated in laboratory and field. The main components of the harvester were digging, conveying and separating units. Six different shape digging blades were evaluated for the digging efficiency. The minimum mean draft of 625.6N was observed for inverted V- shaped blade. The optimal design values of variables like length, speed ratio and slope of the elevator were determined as 1.2 m, 1.25:1 and 15Â°, respectively. During the field evaluation, the prototype onion digger, with the above design values, performed as per the recommended standards with digging efficiency 97.7%, separation index 79.1%, bulb damage 3.5%, fuel consumption 4.1 litre/ha (12.81 litre/ha) and draft 10.78kN. The saving in cost of onion digging/ha with the use of the developed digger in comparison to manual was found to be `1170/ha.